2007
DOI: 10.1016/j.jasms.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

New insights in the formation of deoxynucleoside adducts with the heterocyclic aromatic amines PhIP and IQ by means of ion trap MSn and accurate mass measurement of fragment ions

Abstract: The formation of adducts by reaction of active metabolites of two heterocyclic aromatic amines (NHOH-PhIP and NHOH-IQ) at nucleophilic sites of deoxynucleosides has been studied by LC-MS n analyses of the obtained reaction mixtures. Sequential MS 3 experiments were carried out on an ion trap mass spectrometer to gain extensive structural information on each adduct detected in the first MS step. Attribution of ions was supported by accurate mass measurements performed on an Orbitrap mass analyzer. Particular at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Finally, no depurination induced by the adduct formation was detected on any modified sequence. This result is in agreement with previous results obtained from reactions of PhIP and IQ with deoxynucleosides, 38 which showed that the alkylation process of nucleobases by these HAAs did not involve the destabilization of their sugar-base bond.…”
Section: Sequencing Of Oligonucleotidessupporting
confidence: 93%
See 3 more Smart Citations
“…Finally, no depurination induced by the adduct formation was detected on any modified sequence. This result is in agreement with previous results obtained from reactions of PhIP and IQ with deoxynucleosides, 38 which showed that the alkylation process of nucleobases by these HAAs did not involve the destabilization of their sugar-base bond.…”
Section: Sequencing Of Oligonucleotidessupporting
confidence: 93%
“…40 On the other hand, IQ is known to be able to generate three isomeric adducts with dG, namely dG-C8-IQ, which is the major one, dG-N 2 -IQ and dG-N7-IQ. 38 However, only one adduct has been observed under our synthetic conditions. Here again, taking into account data obtained on deoxynucleosides, this modification of oligonucleotides by IQ likely corresponds to the formation of a G-C8-IQ adduct.…”
Section: Sequencing Of Oligonucleotidesmentioning
confidence: 69%
See 2 more Smart Citations
“…The LTQOrbitrap has also been used to analyze intact small (3-10 kDa) (Bredehöft, Schänzer, & Thevis, 2008;Thevis et al, 2006a;Thevis, Thomas, & Schänzer, 2008b), medium (10-25 kDa) (Macek et al, 2006;Waanders, Hanke, & Mann, 2007) and large ($150 kDa) (Zhang & Shah, 2007) proteins where the MS n capability of the LIT coupled with the high performance features of the orbitrap can facilitate unambiguous determination of the charge states of fragment ions, as well as identification of PTMs by database searching. The high performance attributes of this hybrid mass spectrometer have also found applications in environmental chemistry (Barceló & Petrovic, 2007;Krauss & Hollender, 2008), drug and metabolite analysis (Breitling, Pitt, & Barrett, 2006;Cuyckens et al, 2008;Ding et al, 2007;Karu et al, 2007;Li et al, 2007a;Lim et al, 2007Lim et al, , 2008Madalinski et al, 2008;Nielen et al, 2007;Peterman et al, 2006;Ruan et al, 2008;Thevis et al, 2005;Thevis, Kamber, & Schänzer, 2006b;Thevis, Krug, & Schänzer, 2006c;Thevis et al, 2006dThevis et al, ,e, 2007aThevis et al, , 2008aZhu et al, 2007), lipidomics (Davis et al, 2008;Ejsing et al, 2006;Schwudke et al, 2007;Silipo et al, 2008), small-molecule (Chen et al, 2007b) and reaction product (Jamin et al, 2007) identification, as well as molecular structure characterization using hydrogen/deuterium exchange measurements (Chen et al, 2007a;...…”
Section: Introductionmentioning
confidence: 99%